Five on kirrin island again - Blyton, Enid (Hodder Children's London, 2001)
When Uncle Quentin announces that he will be spending time alone on Kirrin Island and refuses to say why, the Famous Five wonder what he is up to and become even more concerned when they discover that someone else is on the island spying on him